Objective characterization of the relative afferent pupillary defect in MS - Blazek, Paul; Davis, Scott L.; Greenberg, Benjamin M.; Conger, Amy; Conger, Darrel; Vernino, Steven; Beh, Shin; Stuve, Olaf; Saidha, Shiv; Ratchford, John N.; Green, Ari; Calabresi, Peter A.; et al. (Journal of the neurological sciences, 2012)
To develop an objective and precise neurophysiologic method from which to identify and characterize the presence and magnitude of relative afferent pupillary defects (RAPD) in patients with MS. Binocular infrared pupillometry was performed in 40 control subjects and 32 MS patients with RAPDs, using two precisely defined sequences of alternating light flashes (right–left and left–right). We analyzed three distinct pupillary metrics in response to light stimulation. These included percent diameter change (DC), constriction curve area (CCA), which measures change in diameter over time, and the phase-plane curve area (PCA) which measures change in diameter with change in velocity. Direct and consensual response ratios (for each eye) were computed and analyzed for each metric in response to both the first flash (i.e. first phase) and second flash (i.e. second phase) of the ‘swinging flashlight’ test. Second flash pupillary response metric asymmetry ratios yielded the highest discriminatory power for RAPD detection. Receiver operating characteristic areas under the curve for each of the pupillary metric response asymmetry ratios were as follows: diameter change: 0.97; constriction curve area: 0.96; phase-plane curve area: 0.95 (p<0.0001 for all comparisons compared to normal subjects). The sum of these three squared ratios (SSR) yielded a combined metric with the greatest discriminatory power (receiver operator characteristic area under the curve=0.99). Second flash (i.e. the second phase of the swinging light test) pupillary metric response asymmetry ratios are highly sensitive and specific for the confirmation and characterization of an RAPD in patients with MS. This objective neurophysiologic method may be useful for studying the relationship between a stereotyped reflex, and nervous system architecture, with potential ramifications for detecting and monitoring neuroprotective and restorative effects of novel agents in MS treatment trials.